(3gOjI GdCUObGA hGdCMHGH aj GdUHQ hGdEMJSGH dKeQI TLQI Bd YeQ Hf GdNWGHs - (3CMeO Hf YHO GdWja GdHQHjQ,J (B1228 (3g` s ((3eMeO Hf UGdM GdcjdGfi GdTGaYi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd TjNfG GdSjO CMeO GdHQHjQ (B: (3GdMeO ddg GdPi dGjchf YHO g MbkG EdG ef QVi HJbOjQg hSYi ai ESbGW JOHjQg , hCUZi HCPf aDGOg Edi eG jbhdg gGJa GdMb ef QGFb EfTGOg s
(3BNQgG (B:s
(3hbO NJeJ cCS gPg GdQSGdI HeSc gPg GdCHjGJ QGLjkG Cf Jchf eY bUhQgG dOjce ai CYdG GdWHbGJ GfJgi bGd GdYGQa GdefGhi s
(3HgG fXGe GdJYbjHIs
(3HChdgG hbajI HGSe YdGdeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi eDQN SfI (B1373(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3HjQhJ , LeYjI GdebGUO GdESdGejI (B- (3eYgO GdOQGSGJ GdESdGejI (B((3hYX hEQTGO (B181/41) s
Keywords: (3Gdabg GdESdGejs